2022
DOI: 10.1007/s42452-022-05184-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of axial loading on dynamic response of laterally loaded single piles in liquefiable layered soil of Kolkata city considering nonlinearity of soil

Abstract: In the present study, an advanced nonlinear finite-element based 3D numerical study has been carried out to investigate the effects of axial loading on dynamic response of soil-pile system in liquefiable layered soil deposits of Kolkata city. An advanced soil constitutive law based on multi-yield surface plasticity model implemented in fully-coupled u-p formulation is adopted for soil-fluid interaction and pore water pressure development reasonably. The present model is validated with the past experimental res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Studies have observed that piles at shallow depths cannot transfer inertia forces, and kinematic conditions are more effective at these depths [1,2]. There are many numerical and experimental studies on kinematic interaction analyses of piles in the literature [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have observed that piles at shallow depths cannot transfer inertia forces, and kinematic conditions are more effective at these depths [1,2]. There are many numerical and experimental studies on kinematic interaction analyses of piles in the literature [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Mallick et al [12] examined the dynamic effects of the pile-soil system under axial loading in liquefiable soil layers using the 3D finite element method. In the study, an advanced soil strength law based on a multi-surface plasticity model was used for soilfluid interaction and pore water pressure development.…”
Section: Introductionmentioning
confidence: 99%